İdrar yolu enfeksiyonundan korunmada sağlık inanç ölçeği - Kaçar, Seda Fatma (My University, 2025)
Amaç: Yetişkin kadın bireylerin idrar yolu enfeksiyonuna yönelik sağlık inançlarını ölçecek model temelli, geçerli ve güvenilir bir ölçüm aracı geliştirmek amaçlanmıştır. Gereç ve Yöntem: Geliştirilen ölçeğin kuramsal yapısını Sağlık İnanç Modeli oluşturmuştur. Literatür incelenerek hazırlanan madde havuzu kapsam geçerliliği için uzman görüşüne sunularak sonuçları Lawshe tekniği ile değerlendirilmiştir. Veriler araştırmaya katılmaya gönüllü 18-65 yaş arasında 364 kadından online anket yöntemi ile toplanmıştır. Araştırmanın istatistiksel analizinde SPSS 21.0 ve AMOS paket programları kullanılmıştır. Ölçeğin yapı geçerliliğini saptamak amacıyla açımlayıcı ve doğrulayıcı faktör analizleri; güvenilirliğini saptamak amacıyla madde-toplam korelasyonu ve Cronbach alfa iç tutarlık analizi kullanılmıştır. Bulgular: Uzman görüşleri sonucu kapsam geçerlilik ölçütünü sağlamayan 6 madde ölçekten çıkarıldıktan sonra ölçeğin kapsam geçerlik indeksi 0,90 olarak saptandı. Açımlayıcı faktör analiziyle değişkenlerin toplam varyansın %55,85’ini açıkladığı bulundu. Ölçeğin iç tutarlık değeri (α=0,888) olarak bulunmuştur. Sonuç: Bu tez çalışması sonucunda 26 madde ve 6 alt boyuttan (algılanan yarar, algılanan engel, algılanan ciddiyet, algılanan duyarlılık, sağlık motivasyonu ve öz yeterlilik) oluşan geçerli ve güvenilir bir ölçüm aracı elde edilmiştir. Ölçeğin toplam puanı İdrar Yolu Enfeksiyonundan Korunmada Sağlık İnancı puanını verir. Ölçekten en yüksek 130, en düşük 26 puan alınabilir. Geliştirilen bu ölçüm aracının yetişkin kadınlarda idrar yolu enfeksiyonundan korunmada sağlık inancını saptamak amacıyla uygulanması önerilir.

Objective: The aim of this study was to develop a model-based, valid and reliable measurement tool to measure the health beliefs about protection against urinary tract infections in women. Materials and Methods: The theoretical structure of the developed scale was created by the Health Belief Model. The item pool prepared by examining the literature was presented to expert opinion for content validity and the results were evaluated using the Lawshe technique. Data were collected by online survey method from 364 women between the ages of 18-65 who volunteered to participate in the research. SPSS 21.0 and AMOS package programs were used in the statistical analysis of the research. Confirmatory and exploratory factor analyses were used to ensure the structural validity of this scale; Item-total correlation and Cronbach's alpha internal consistency analysis were used to determine its reliability. Results: As a result of expert opinions, after 6 items that did not meet the content validity criterion were removed from the scale, the content validity index of the scale was determined as 0.90. With exploratory factor analysis, it was found that the variables explained 55.85% of the total variance. The internal consistency value of the scale was found to be (α=0.888). Conclusion: As a result of this thesis study, a valid and reliable measurement tool consisting of 26 items and 6 sub-dimensions (perceived benefit, perceived obstacle, perceived seriousness, perceived sensitivity, health motivation and self-efficacy) was obtained. The total score of the scale gives the Health Belief score in Protection from Urinary Tract Infection. The highest score from the scale can be 130 and the lowest score can be 26. It is recommended that this developed measurement tool be applied to determine health beliefs in preventing urinary tract infection in adult women.
Health belief scale in the prevention of urinary tract infection
Keywords: Halk sağlığı hemşireliği; health belief scale; İdrar yolu enfeksiyonu; kadınlar; Public health nursing; sağlık inanç ölçeği; Urinary tract infection; women